(untitled) (Semiárida, 2020)
During the months of november-december 1987, the produtive result of dry matter was observed in six cultivars of Amaranthus by means of using pots placed in greenhouse, adding the followiyg quantities of fluorine as of sodium fluorine: 8 mg kg ,12 mg Kg and 16 mg Kg. The yield result of dry matter, obtained 35 days after having been sown , proved that Amaranthus hypochondriacus L. type "Mercado" (Rodale 81S -1024) showed a highly superior result with the addition 12 mg Kg and 16 mg Kg of soluble fluorine. The rest of the cultivars did not present important differences.